A Framework for Building Research Partnerships with First Nations Communities. (January 2014) - Bharadwaj, Lalita
Solutions to complex health and environmental issues experienced by First Nations communities in Canada require the adoption of collaborative modes of research. The traditional "helicopter" approach to research applied in communities has led to disenchantment on the part of First Nations people and has impeded their willingness to participate in research. University researchers have tended to develop projects without community input and to adopt short term approaches to the entire process, perhaps a reflection of granting and publication cycles and other realities of academia. Researchers often enter communities, collect data without respect for local culture, and then exit, having had little or no community interaction or consideration of how results generated could benefit communities or lead to sustainable solutions. Community-based participatory research (CBPR) has emerged as an alternative to the helicopter approach and is promoted here as a method to research that will meet the objectives of both First Nations and research communities. CBPR is a collaborative approach that equitably involves all partners in the research process. Although the benefits of CBPR have been recognized by segments of the University research community, there exists a need for comprehensive changes in approaches to First Nations centered research, and additional guidance to researchers on how to establish respectful and productive partnerships with First Nations communities beyond a single funded research project. This article provides a brief overview of ethical guidelines developed for researchers planning studies involving Aboriginal people as well as the historical context and principles of CBPR. A framework for building research partnerships with First Nations communities that incorporates and builds upon the guidelines and principles of CBPR is then presented. The framework was based on 10 years' experience working with First Nations communities in Saskatchewan. The framework for research partnership is composed of five phases. They are categorized as the pre-research, community consultation, community entry, research and research dissemination phases. These phases are cyclical, non-linear and interconnected. Elements of, and opportunities for, exploration, discussion, engagement, consultation, relationship building, partnership development, community involvement, and information sharing are key components of the five phases within the framework. The phases and elements within this proposed framework have been utilized to build and implement sustainable collaborative environmental health research projects with Saskatchewan First Nations communities.